Real exchange rate and export performance in Argentina, 2002–2008 - Palazzo, Gabriel Martín (2017)
Between 2002 and 2008, Argentina experienced a phase of very high and sustained economic growth. During this period, macroeconomic policy aimed to preserve a stable and competitive real exchange rate (SCRER). There is controversy on whether the SCRER policy was a key factor fostering growth and, even more, on whether it helped promote the expansion of tradable activities and exports. We use a methodology to detect episodes of export surges among Argentina’s export industries and find that labor-intensive industries—especially low- and medium-technology manufactures—experienced the highest proportion of export surges within this period. We also find that between 1980 and 2015, the highest proportion of surges in total exports occurred during the 2003–8 period. The performance of export of services was also particularly dynamic during this period. This evidence suggests that the SCRER policy was instrumental for export surges in Argentina during 2002–8.